The trajectory of fashion from 1980 to 2022: The view of women in a city in the Midwest of Minas Gerais - Santos, Rogério Junio dos; Morais , Gleison Silva; Carvalho , Victor Hugo (Seven Editora, 2024)
Fashion is something that goes beyond covering the body, it conveys the individual's relationship with society and their individual perception of events in different contexts, environmental, social, religious and political. The study aims to verify the perception of women, ≥35 years old, regarding the influence of globalization on consumption behavior and accessibility to fashion and beauty in the 80s, 90s and also "millennia" (2000 - 2023); and thus understand how the people who live in the city of Santo Antônio do Monte - MG perceive fashion in each of these times. This is a cross-sectional study of a qualitative and quantitative nature. Initially, 133 individuals answered the questionnaire formulated on the Google Forms platform; After tabulating the results in Excel 2018 software, 127 individuals with a mean age of 44.77 (±8.05) years were analyzed and reported after following the exclusion criteria. In general, the globalization process has positively influenced the perception, desire and consumption of women in Santo Antônio do Monte - MG, where it can also be seen that the more information available there is, the greater the demand for fashion, hair and makeup trends. It is suggested that further studies be carried out in order to highlight how important it is to understand how political, economic, social and environmental contexts can influence fashion, consumption, accessibility, desire and perception of women, and audiences in general in inner cities.    DOI:https://doi.org/10.56238/sevened2024.009-008